Простушка: лгу не могу - Кеплингер Коди. (Виноваты звезды, 2017)
Экземпляры: Новомоньинская библиотека (20171215) / Инвентарный номер: 204769 / Цена: 258.42 / Авт.знак: К 35 / ГРНТИ: 17.82 / ББК: 84(7Сое)